Investigação etnobotânica entre os Guarani Mbya de Tekoa Pyau - Galante, Luciana (2011)
This study analyzes the relationship between the Guarani community from Tekoa Pyau with the environment through an ethnobotanical approach, in particular with the vegetal universe. There have been several speculations that the people in this community are deprived from their cultural references, due to the fact that they live in a small area adjecent to a Conservation Unit. The Atlantic Forest is an ideal site for the nhandereko Gurani way of life and it is surrounded by symbolysm. Such symbolic references often pertain to a refined knowledge about the natural resources, which is of extreme importance to the Guarani people. The Jaraguá State Park is not only a site for natural resources. Most importantly, there is evidence that it has a cultural collection , given that certain vegetables were sacredly named by the Guarani. The several plants and animals provided by Nhanderu (our Father) enabled the Guarani to survive and were particularly associated to their myths. The Guarani strive to maintain such knowledge. Yet, they do so through a particular traditional education, which includes orality, life experience, myths and rituals. In addition, the Guarani have been attempting to enagage in dialogs with people in our society as a way to be heard, understood, and equally important, to have their knowledge acknowledged and respected